THE APPLICATION OF PHENOMENON-BASED LEARNING IN TEACHING ENGLISH TO HIGHER EDUCATION STUDENTS (NON-PHILOLOGICAL DEPARTMENTS) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Annotation. The study reinforces the theoretical understanding of PhenoBL as not merely a teaching method but a new way of thinking that promotes relevant, innovative, substantive, and timely learning of non-philological departments. Its successful implementation relies on teachers' collaborative efforts, theoretical understanding, and adaptability, with positive outcomes for both educators and learners. The study underscores the need for continued exploration into integrating foreign languages within this innovative pedagogical framework.